THE EFFECTIVENESS OF THE PROBLEM-BASED LEARNING (PBL) MODEL WITH AN EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) APPROACH IN IMPROVING STUDENTS' ENVIRONMENTAL AWARENESS - Aida Amalia Fadilah; Faizah, Ulinnuha Nur (INSECTA: Integrative Science Education and Teaching Activity Journal, 2025)
The environmental awareness of students at SMPN 3 Ponorogo is still lacking as evidenced by results of initial observations through a pretest in class VII with material Ecology and Biodiversity in Indonesia, especially sub-chapter Influence of Human Actions on Environment, obtained an average of 48,83%. This study aims to determine the effectiveness of PBL model with ESD approach to environmental care skills of class VII students. The method used in this study is a quantitative approach with a True Experiment design with experimental and control classes. The sampling technique used is Simple Random Sampling, the sample is students of class VII B and VII F, each class consisting of 30 children. Data collection techniques with tests through pretest and posttest. Data analysis techniques used included normality tests, homogeneity, t-test (independent), N-Gain, and effect cohend. Based on the research results, it is known that the average value of experimental class' environmental care ability for environmental insight indicator is 80 to 90, the maintenance, preservation, and skills indicator is 90 to 98. PBL learning model and ESD approach proved effective in terms of environmental care skills as evidenced by the results of t-test (independent) which showed in experimental class and control class. The results of the N-Gain and effect cohend tests showed that experimental class was more effective in improving students' environmental care skills than control class.